2016
DOI: 10.1515/hepo-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical composition of the essential oils from different parts of Thuja occidentalis L. ‘Brabant’ and T. occidentalis L. ‘Smaragd’

Abstract: S u m m a r yIntroduction: Thuja occidentalis 'Brabant' and T. occidentalis 'Smaragd' are widely planted as decoration in parks and as hedges in domestic gardens in Poland. Objective: The aim of the study was to determine the yield and the composition of essential oils from different parts of these cultivars. Methods: The essential oils were obtained by hydrodistillation, and then analyzed by GC/MS. Results: Over seventy compounds were identified. The oils from leaves, twigs with leaves and twigs without leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The qualitative composition of most constituents complies with the literature data. Some differences were also observed, such as the higher content of sabinene, terpien-4-ol, and bornyl acetate [16,45,46]. Keita et al [13] identified 22 EO components from T. occidentalis, with α-thujone (49.60%), fenchone (14.03%), and β-thujone (9.05%) being dominant, as in the present experiment.…”
Section: Chemical Composition Of Eotosupporting
confidence: 56%
See 3 more Smart Citations
“…The qualitative composition of most constituents complies with the literature data. Some differences were also observed, such as the higher content of sabinene, terpien-4-ol, and bornyl acetate [16,45,46]. Keita et al [13] identified 22 EO components from T. occidentalis, with α-thujone (49.60%), fenchone (14.03%), and β-thujone (9.05%) being dominant, as in the present experiment.…”
Section: Chemical Composition Of Eotosupporting
confidence: 56%
“…Some diterpenes were also found in this essential oil, which is a group of terpenoids characteristic of coniferous trees. Byerene was the dominant compound among this group (1.1-12.8%) [16]. The correlation between essential oil composition and plant origin is well known.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, a previous study focusing on Ricinus communis EO aerial parts in Tunisia showed that oxygenated monoterpenes had the highest percentage with 75.61% with α-thujone (31.71%) and 1,8-cineole (30.98%) as the main compounds of this EO. [40] Thus, according to Lis et al [41] , the chemical composition of the EO depends on several factors such as plant organ (leaves, flowers, stems, etc.). In fact, depending on this factor, several EOs of the same plant with different chemical compositions and biological activities can be formed.…”
Section: Essential Oil Yields and Chemical Compositionmentioning
confidence: 99%